The Impact of Adopting Social Responsibility Dimensions on Customer Satisfaction (A field study on telecommunications companies in Lattakia) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to demonstrate the impact of adopting the dimensions of social responsibility through (economic, legal, ethical, humanitarian) on customer satisfaction in telecom companies in Lattakia.The researcher followed the descriptive analytical approach in her study, and a group of methods, including relying on the collection of secondary and primary data, through two questionnaires that were developed based on previous studies, and the first was distributed to (45) managers in telecommunications companies, from which (40) were retrieved, and they were (37) A questionnaire is valid for analysis, and the second questionnaire was distributed to (123) corporate clients, from which (119) were recovered, and (114) were valid for analysis. Then, the SPSS program was relied upon as a tool for analyzing the available data, The researcher used the following statistical methods:Ratios and repetitions.Descriptive statistics: arithmetic means, standard deviations.One-sample T testSpearman correlation coefficient.The study reached a number of results, including: the existence of a significant relationship between economic responsibility and customer satisfaction in telecommunications companies in the city of Lattakia, and the existence of a significant relationship between economic responsibility and customer satisfaction in telecommunications companies in the city of Lattakia according to customers’ answers, and the existence of a relationship Significant significance between legal responsibility and customer satisfaction in telecommunications companies in the city of Lattakia, according to the managers' answers